Organizing women in contemporary Russia : engendering transition - Sperling, Valerie (Cambridge University Press, 1999)
This book offers a rich and clearly-written analysis of the women's movement in contemporary Russia. It tells the engaging story of the women's movement's formation and development in a country undergoing a radical economic and political transition from communist rule.
Keywords: Feminism -- Russia (Federation); Women -- Russia (Federation) -- Social conditions.; Russia (Federation) -- Social conditions -- 1991-; Féminisme -- Russie.; Femmes -- Russie -- Conditions sociales.; Russie -- Conditions sociales -- 1991-; SOCIAL SCIENCE -- Feminism & Feminist Theory.; Feminism; Social conditions; Women -- Social conditions; Russia (Federation); Organisation; Soziale Situation; Russland; Frau; Vrouwenbeweging.; Since 1991; Electronic books.